Sultamicillin in the treatment of gonorrhoea caused by penicillin sensitive and penicillinase producing strains of Neisseria gonorrhoeae. Issue 5 (October 1983) - Atia, W A; Emmerson, A M; Holmes, D
Abstract : A single oral dose of 2 g of sultamicillin and 1 g of probenecid was effective in the treatment of men with uncomplicated gonococcal urethritis caused by both penicillin sensitive strains of Neisseria gonorrhoeae and penicillinase producing strains of N gonorrhoeae (PPNG). Of 94 infected men who attended for at least one follow up examination, 91 (97%) were cured. The remaining three (3%) patients were still infected at follow up. Two of these patients had been re-exposed to an infected partner and were considered to be possible reinfections, while the third was deemed a treatment failure. Six of the 94 patients were infected with PPNG strains and all were successfully treated. Plasmid analysis of the PPNG strains showed Asian and African types both with and without transfer plasmid.